Pengaruh Stabilitas Keuangan terhadap Kecurangan Laporan Keuangan pada Perusahaan Konstruksi di Indonesia Stock Exchange Industrial Classification - Wahyuningsih Wahyuningsih; Winda Ningsih; Cepi juniar Prayoga; Ai Lisna (Fakultas Ekonomi Universitas Garut, 2025)
The research study aims to determine the effect of financial stability on the practice of financial statement fraud in construction entities in the Indonesia Stock Exchange Industrial Classification. The phenomenon of fraud in financial statements is a crucial focus because it has the potential to undermine investor confidence and threaten the existence of company operations. A quantitative approach is applied through data collection from literature reviews and secondary sources. Analysis of the relationship between variables is carried out using simple linear regression. This research reveals that the company's financial stability does not have significant implications for the frequency of fraud in financial statements in the construction sector.